Photoinitiated Dispersion Polymerization of Crosslinked Polymer in Polar Solvents: Effect of Reaction Parameter on Morphology, Size and Size Distribution and Yield - R., Mahmod; M. Z., Yahya; Norhayati, Abdullah (Informatics Publishing Limited, 2017)
Crosslinked polymer beads were prepared by photoinitiated dispersion polymerization in a mixture of ethanol and water. In this study, the effect of types of photoinitiator, types of monomer and reaction times on particles morphology, size and size distribution and yield were investigated. Better quality of poly(st-co-EGDMA-co-VBC) obtained compared to poly (methylmethacrylate-co- EGDMA-co-VBC). However, the yield of poly(st-co-EGDMA-co-VBC) lower than poly (methylmethacrylate-co-EGDMA-co-VBC). On this regard, poly(methylmethacrylate-co-EGDMA-co-VBC) was selected to investigate further. Changing the types of photoinitiator managed to increase the quality and size of poly (methylmethacrylate-co-EGDMA-co-VBC) particles but yield obtained was decreasing. Meanwhile, longer reaction time leading to high yield and bigger size of poly (methylmethacrylate-co-EGDMA-co- VBC) particles but with lower quality. For all cases, FTIR analysis proved all functional groups have successfully attached to the polymeric backbone.